2022
DOI: 10.31234/osf.io/ha2tf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interventions to Reduce Partisan Animosity

Abstract: Rising partisan animosity is linked to less support for democracy and more support for political violence. Here we provide a multi-level review of interventions designed to improve partisan animosity, which we define as negative thoughts, feelings, and behaviors towards a political outgroup. We introduce the TRI framework for the three levels of interventions—Thoughts (correcting misconceptions, highlighting commonalities), Relationships (building dialogue skills, fostering positive contact), and Institutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 122 publications
0
10
0
Order By: Relevance
“…For instance, Lyons (2022) argues that "older Americans do not suffer a particular deficit in such skills and interventions aiming to improve the quality of online news sharing may be better served by instead targeting the increasing partisan animosity among these news consumers" (p. 24). Interventions to reduce partisan animosity propose not only to correct misperceptions (and meta-misperceptions) about the outgroup, but also to highlight commonalities so that partisan identity encompasses the outgroup, develop dialogue skills to communicate across political divides, foster positive contact, and address the institutional factors that give rise to a polarizing environment (Hartman et al, 2022). If successful, such interventions may have a variety of positive effects that goes beyond reducing belief in misinformation.…”
Section: Reduce Partisan Animositymentioning
confidence: 99%
“…For instance, Lyons (2022) argues that "older Americans do not suffer a particular deficit in such skills and interventions aiming to improve the quality of online news sharing may be better served by instead targeting the increasing partisan animosity among these news consumers" (p. 24). Interventions to reduce partisan animosity propose not only to correct misperceptions (and meta-misperceptions) about the outgroup, but also to highlight commonalities so that partisan identity encompasses the outgroup, develop dialogue skills to communicate across political divides, foster positive contact, and address the institutional factors that give rise to a polarizing environment (Hartman et al, 2022). If successful, such interventions may have a variety of positive effects that goes beyond reducing belief in misinformation.…”
Section: Reduce Partisan Animositymentioning
confidence: 99%
“…Considering US attitudes towards immigration, Captari et al (2019) found that greater CH corresponded with lower prejudice, lower perceived threat from the other and greater openness to immigration. Promoting constructive dialogue and positive intergroup contact may be effective relational or systemic level interventions to counteract polarisation (Captari et al, 2019; Hartman et al, 2022), whereas individual‐level interventions can focus on challenging preconceived notions and falsehoods about the other and identifying points of shared humanity, that is, “possible bridges” between self and other (Hartman et al, 2022; Rober & De Haene, 2014, p. 18). Examination of the effectiveness of CH interventions to bridge differences and improve relational dynamics is greatly needed.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the current research suggests that messages by recently‐swayed skeptics that emphasize commonalities and appreciate different group virtues should be more effective. Two registered reports confirmed behavioral effects of message source, indicating that ISE processes are prime‐candidates to consider to mend societal divides (Hartman et al., 2022).…”
Section: Practical Implicationsmentioning
confidence: 92%